Antimicrobial and Antibiofilm Activity of Monolaurin against Methicillin-Resistant Staphylococcus aureus Isolated from Wound Infections - Shimaa Salah Hassan Abd El-Ghany; Ahmed Farag Azmy; Ahmed Osama EL-Gendy; Rehab Mahmoud Abd El-Baky; Ahmad Mustafa; Mohammed A. S. Abourehab; Mohamed E. El‐Beeh; Reham Ali Ibrahem (International Journal of Microbiology)
Background. Methicillin-resistant Staphylococcus aureus (MRSA) is one of the major pathogens associated with life-threatening infections, showing resistance to various antibiotics. This study aimed to assess the influence of monolaurin on biofilm-forming MRSA. Methods. The agar dilution method determined the minimum inhibitory concentration (MIC) of monolaurin against MRSA isolates and explored its impact on the resistance profile of selected antibiotics. The assessment of combined therapy involving monolaurin and antibiotics was conducted using fractional inhibitory concentration (FIC). The tissue culture plate strategy appraised monolaurin’s antibiofilm activity and its inhibitory concentration (IC50), with assessment via scanning electron microscopy. Reverse transcription polymerase chain reaction (RT-PCR) discerned a monolaurin effect on the expression of the icaD gene. Results. Monolaurin exhibited MIC values ranging from 500 to 2000 μg/mL. FIC index showed a synergistic effect of monolaurin with β-lactam antibiotics ranging from 0.0039 to 0.25 (p<0.001). Among the 103 investigated MRSA isolates, 44 (44.7%) displayed moderate biofilm formation, while 59 (55.3%) were strong biofilm producers. Antibiofilm activity demonstrated concentration dependence, confirming monolaurin’s capacity to inhibit biofilm formation and exhibited strong eradicating effects against preformed MRSA biofilms with IC50 values of 203.6 μg/mL and 379.3 μg/mL, respectively. Scanning electron microscope analysis revealed reduced cell attachments and diminished biofilm formation compared to the control. The expression levels of the icaD gene were remarkably reduced at monolaurin concentrations of 250 and 500 μg/mL. Conclusion. Monolaurin had significant inhibitory effects on MRSA pre-existing biofilms as well as biofilm development. So, it can be employed in the treatment of severe infections, particularly those associated with biofilm formation including catheter-associated infections.